4(x-6)=-2(x+3)

Simple and best practice solution for 4(x-6)=-2(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-6)=-2(x+3) equation:


Simplifying
4(x + -6) = -2(x + 3)

Reorder the terms:
4(-6 + x) = -2(x + 3)
(-6 * 4 + x * 4) = -2(x + 3)
(-24 + 4x) = -2(x + 3)

Reorder the terms:
-24 + 4x = -2(3 + x)
-24 + 4x = (3 * -2 + x * -2)
-24 + 4x = (-6 + -2x)

Solving
-24 + 4x = -6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-24 + 4x + 2x = -6 + -2x + 2x

Combine like terms: 4x + 2x = 6x
-24 + 6x = -6 + -2x + 2x

Combine like terms: -2x + 2x = 0
-24 + 6x = -6 + 0
-24 + 6x = -6

Add '24' to each side of the equation.
-24 + 24 + 6x = -6 + 24

Combine like terms: -24 + 24 = 0
0 + 6x = -6 + 24
6x = -6 + 24

Combine like terms: -6 + 24 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 0-2x+1=0 | | 2w-6=126 | | z-4z=9z-6-z | | (-7+8x)-(x-1)=3x+6 | | 6x-1=2x-21 | | 25.94=5g+3.69 | | z+6=-17 | | 2(3x)+2(x)=320 | | 175-75+48750=50750-150 | | 3x(9-8)+7-11= | | 12z-4z+8=-16 | | 7z-z=-1+3z-1-1 | | 4x+3=6+2x+25 | | 4x^2+4x-5=2x(x+3)-1 | | 1.52g-11=0.40 | | -2-2x=6x-50 | | 0.24p+1.17=1.8 | | 45+90x=585 | | 9x+8y=13.83 | | -5r-5r=4-8r-4r | | 48750-75+175=50750-150 | | 0.24p+1.17=1.29 | | -2x-6=2(2x-3) | | x=6.9375+-0.4375y | | -9=3(-c+2) | | 1X+4X=58 | | -20(y+2)+6(4y-4)=3(y-6)+12 | | -0.24p+1.602=1.8 | | 12x-3=4x | | 3(x-2)-4=4x-2 | | 9y=2y+35 | | v^2-2=65 |

Equations solver categories